PERAN ORANG TUA DALAM MEMBENTUK KARAKTER TANGGUNG JAWAB ANAK SMP PADA ERA PANDEMI - Nurul Ikhsaniyah; Rahmanu Wijaya (Kajian Moral dan Kewarganegaraan, 2022)
This research for describing role of parents who created responsibility junior high school characters at pandemic in Sajen Village and for knowing factors that given impact when do this role. This research using a qualitative research approach with a descriptive design. Informants in this research are parents who have child in the junior high school with the five informants. This research did in Sajen village. Data collected by in-depth interview, observation, and documentation. This research focus on role of parents in building responsibility character and impact factors when implemented it. This research using Role Theory from Biddle and Thomas. The source is parents having role like a educator, mentor, motivator, facilitator, and like a friend. This role such a giving an instruction of talent and interest, giving a motivation so the children will be happy when study. There were factors what giving impact like a change of education, the economic level, time availability. Connection between role theory and this research is parents wishes for doing the role in this character. Norm, like a rule from parents to children. Performances, like by doing all of the role and it giving good character in life. Evaluation and sanction , like an evaluation of parents to children character and if deviate, they get a sanction. Keyword: role of parents, responsibility character, pandemic era